SOLID LOSS AND WEIGHT GAIN IN PRAWNS DURING STORAGE IN ICE - MATHEN, CYRIAC; THOMAS, FRANCIS (Fishery Technology, 2017)
Loss of solids from and gain in weight of the meat of whole prawn and prawn meat stored in ice have been studied to explain the mechanism of solid loss. Two stages are identified in this penomenon. In the first stage water is absorbed without loss of solids resulting in a maximum increase in weight. In the second stage both solids and water are lost resulting in gradual decrease in weight from the maximum reached but not reaching the original weight. It is inferred that whole prawns stored in ice up to two days give the maximum peeled yield without loss of nutrients and at the same time making the peeling process easier.